Google Meet Application as an Online Learning Media for Descriptive Text Material - Aswir Aswir; Muhammad Sofian Hadi; Fatimah Rosiana Dewi (Universitas Cokroaminoto Palopo, 2021)
The Covid-19 pandemic has resulted in all activities being carried out online from home, including teaching and learning activities. So the use of online-based platforms can be a solution to the learning process at this time continues to run smoothly. One application that can be used is Google Meet which is a video communication service. This study aims to explain the use of Google Meet in the learning process of Descriptive Text material in class 10 IPS 4 MAN 4 Jakarta, which includes the advantages and disadvantages that are felt in the implementation of learning this material using Google Meet. This research uses qualitative research with descriptive methods where the research results are obtained through observation and interviews which are then analyzed by describing them. The results of the study found that Google Meet is suitable for delivering Descriptive Text learning material while speaking practice for students in class 10 IPS 4. However, this media cannot be used to carry out written assessments so that other media is needed as an additional medium of taking written scores